Nano‐Ligands: Independent Tuning of Nano‐Ligand Frequency and Sequences Regulates the Adhesion and Differentiation of Stem Cells (Adv. Mater. 40/2020). Issue 40 (7th October 2020) - Min, Sunhong; Jeon, Yoo Sang; Jung, Hee Joon; Khatua, Chandra; Li, Na; Bae, Gunhyu; Choi, Hyojun; Hong, Hyunsik; Shin, Jeong Eun; Ko, Min Jun; Ko, Han Seok; Jun, Indong; et al.
Abstract : In article number 2004300, Young Keun Kim, Heemin Kang, and co‐workers report a magnetic nano‐barcoding system that enables unique tunability of ligand frequency and nano‐sequences to effectively regulate stem cell adhesion with no systemic toxicity in vivo. Low‐frequency and terminally sequenced nano‐ligands facilitate focal adhesion, mechanotransduction, and differentiation of stem cells.